2018
DOI: 10.1530/joe-18-0449
|View full text |Cite
|
Sign up to set email alerts
|

Stress rapidly suppresses in vivo LH pulses and increases activation of RFRP-3 neurons in male mice

Abstract: Restraint stress is a psychosocial stressor that suppresses reproductive status, including LH pulsatile secretion, but the neuroendocrine mechamisms underlying this inhibition remains unclear. Reproductive neural populations upstream of gonadotropin releasing hormone (GnRH) neurons, such as kisspeptin, neurokinin B, and RFRP-3 (GnIH) neurons, are possible targets for psychosocial stress to inhibit LH pulses, but this has not been well-examined, especially in mice in which prior technical limitations prevented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 45 publications
3
19
0
Order By: Relevance
“…We have shown for the first time that TMT increases and maintaines elevated CORT secretion in mice. The TMT-induced rise in CORT was maintained for at least 1-hour after termination of the predator odor stress, indicating prolonged HPA axis activation, which has been observed with prolonged restraint stress in mice (47). This indicates exposure to these psychogenic stressors can lead to prolonged HPA axis activation in mice.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…We have shown for the first time that TMT increases and maintaines elevated CORT secretion in mice. The TMT-induced rise in CORT was maintained for at least 1-hour after termination of the predator odor stress, indicating prolonged HPA axis activation, which has been observed with prolonged restraint stress in mice (47). This indicates exposure to these psychogenic stressors can lead to prolonged HPA axis activation in mice.…”
Section: Discussionmentioning
confidence: 73%
“…with prolonged restraint stress in mice (47). This indicates exposure to these psychogenic stressors can lead to prolonged HPA axis activation in mice.…”
Section: Discussionmentioning
confidence: 93%
“…It remains unclear from this experiment whether RFRP neurons suppress reproductive function in direct response to the stressor or indirectly in response to HPA axis-induced glucocorticoid secretion. It should be noted that the period of restraint was limited to 30 min, and stress-induced glucocorticoid release probably only began to occur toward the end of this brief time period (Yang et al, 2018). Therefore, RFRP neurons may activate in direct response to the stressor and interact with GnRH neurons to suppress pulse frequency independently of glucocorticoid levels, on a time scale of minutes.…”
Section: Discussionmentioning
confidence: 99%
“…RFamiderelated peptide-3 (RFRP-3) is a peptide secreted by RFRP neurons that project from the rodent dorsomedial hypothalamus (DMH), and is mostly (but not exclusively) inhibitory to GnRH activity (Ducret et al, 2009;Rizwan et al, 2009;Wu et al, 2009;Ancel et al, 2017). Interestingly, acute restraint stress was shown to suppress LH pulsatility while concomitantly increasing RFRP neuronal activation in male mice (Yang et al, 2018), and the activity of RFRP neurons was also upregulated by restraint stress in male rats (Kirby et al, 2009), suggesting that RFRP neurons may play a role in mediating the suppressive effects of stress on the HPG axis. Furthermore, approximately half of RFRP neurons express glucocorticoid receptors, and the effect of restraint stress on Rfrp gene expression was blocked by adrenalectomy (Kirby et al, 2009), suggesting that adrenal glucocorticoids activate RFRP neurons in stressful situations.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic challenges, such as short‐term fasting and high‐fat diet, are less effective in decreasing LH secretion in GPR147‐deficient male mice, suggesting that the GnIH‐GPR147 inhibitory pathway mediates gonadotropin suppression by metabolic stress . Stressful stimuli also activate GnIH‐ir neurons or increase GnIH expression in rats and mice . It was further shown that GnIH administration activates hypothalamic‐pituitary‐adrenal (HPA) axis in rats, mice, and rhesus monkeys .…”
Section: Mediation Of Stress Responsesmentioning
confidence: 99%